Perbedaan Individu dalam Proses Pembelajaran dan Faktor-faktor yang Mempengaruhinya - Siska Nerita; Jamaris Jamna; Solfema Solfema (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Curriculum development aims to advance education, curriculum development also considers the characteristics of students, because each individual has various differences. Individual differences that need to be considered in the learning process are the basic skills, talents, interests, speed, and learning styles of children. Each individual has a learning style that can be influenced by several factors. Students at PGRI University in West Sumatra have different characteristics, one of which is learning style. This study aims to determine individual differences in the learning process and the factors that influence it. This research was conducted using descriptive analysis with qualitative methods, meaning that the results of data collection for individual differences by distributing questionnaires, and for the factors that influence them are supported by a literature review. The results obtained are the percentage of students' visual learning styles 84.85% good criteria, audio learning styles 78.79% good criteria, and kinesthetic learning 74.49% good enough criteria. Individual differences are influenced by genetic and environmental factors, environmental factors consist of school, family and community. It can be concluded that there are differences for each individual in the learning process. There are 3 types of individual learning that can have implications for learning, namely: auditory, visual, and kinesthetic types. The factors that influence individual differences are genetics and environment. The environment consists of schools, families, and communities. Individual variations have an impact on learning implications for the way teachers plan and implement the learning process.